STRES IZAZVAN ANTROPOGENIM ONEČIŠĆENJEM: TALOŽENJEM KATEKOLAMINA U ERITROCITIMA Scorpaena porcus (Linnaeus, 1758) - Fazio, Francesco; Basova, Marina; Sabri Kesbiç, Osman (University of Zagreb Faculty of Agriculture, 2024)
The sympathoadrenal system plays an essential role in forming the body's response to the action of stimuli of various natures and intensities. The content of deposited catecholamines in peripheral blood erythrocytes is one of the most accessible parameters for an adequate description of the functional activity of the sympathoadrenal system in humans and rats. The aim of the work is to assess the accumulation of catecholamines in erythrocytes of sea ruffs Scorpaena porcus L. at various pollution levels in the bays of Sevastopol. The phenomenon of accumulation of catecholamines in erythrocytes of the peripheral blood of fish is revealed. The concentration of erythrocytes with deposited catecholamines was higher in fish from polluted bays. In 2006, fish from Alexander Bay exhibited a significantly higher erythrocyte content of deposited catecholamines (36.04%) compared to those from the background area (28.19%) and Quarantine Bay (30.74%) (p

Simpatoadrenalni sustav igra bitnu ulogu u formiranju odgovora tijela na djelovanje podražaja različite prirode i intenziteta. Sadržaj deponiranih katekolamina u eritrocitima periferne krvi jedan je od najdostupnijih parametara za adekvatan opis funkcionalne aktivnosti simpatoadrenalnog sustava ljudi i štakora. Cilj rada je procijeniti akumulaciju kateholamina u eritrocitima škarpuna Scorpaena porcus L. pri različitim razinama onečišćenja u zaljevima Sevastopolja. Otkriven je fenomen nakupljanja kateholamina u eritrocitima periferne krvi riba. Koncentracija eritrocita s taloženim kateholaminima bila je veća u riba iz onečišćenih uvala. U 2006. godini, ribe iz Aleksandrijskog zaljeva pokazale su značajno veći sadržaj deponiranih kateholamina u eritrocitima (36,04%) u odnosu na one iz udaljenijeg područja (28,19%) i Karantinskog zaljeva (30,74%) (p
Keywords: anthropogenies pollution; sympathoadrenal system; catecholamine; erythrocytes; simpatoadrenalni sustav; eritrociti; fiziološki pokazatelji; physiological indicators; antropogeno zagađenje; kateholamina